EFFECT OF TEMPERATUiRE ON RESPIRATION OF LABEO FIMBRIATUS (BLOCH) - Kasim, H Mohamad (Indian Journal of Fisheries, 2011)
Labeo fimbriatus (Bloch) was tested at non-lethal temperatures to measure its oxygen uptake both in oxygen dependant and independant zones. The metabolic rate was almost uniform in oxygen independant zone, in oxygen dependant zone reduced drastically and then oxygen level becomes lethal. This species regulated the oxygen consumption at lower rate at extreme high and low temperatures than at intermediary optimum temperatures. The lethal oxygen level was much higher at low temperatures, whereas it was the lowest at optimum temperature. The highest lethal oxygen level at low temperature is attributed to the inhibition in oxygen uptake. Cold-acclimated fish consumed more oxygen than the warm-acclimated fish. The time to death was the highest at low temperature